Video-based biomechanical analysis of an unexpected Achilles tendon rupture in an Olympic sprinter. (5th March 2021) - Loturco, Irineu; De la Fuente, Carlos; Bishop, Chris; Nichioka, Hélio; Lessio, Denise; Moreno, Carlos T.; Pereira, Lucas A.; Carpes, Felipe P.
Abstract: We used image-processing techniques to determine the moment (i.e., image frame) of the Achilles tendon (AT) rupture in an Olympic sprinter. This report may be unique due to the difficulty in conducting motion capture analyses during injury events. Our report includes one female Olympic sprinter, 29 years old (body mass: 56 kg, height: 1.68 m, and body mass index: 19.8 kg/m 2 ) with a high-competitive profile history (2008 and 2012 Olympic Games participation; South American record holder in 100- and 200-m; Pan-American gold medalist in 200-m and 4 × 100-m relay) who suffered a complete AT rupture in the left leg while exercising in the final phase of rehabilitation following an Achilles tendinopathy in the contralateral limb. The greater dorsiflexion found at the moment of the injury and the delayed control of heel position indicated the presence of uncontrolled dorsiflexion, which potentially generated excessive eccentric stress over the tendon and, thus, the AT rupture. Here we discuss the relevance of lower leg alignment, the movements' characteristics, and the history of Achilles tendinopathy in the contralateral leg on the occurrence of the AT rupture.